2012
DOI: 10.1100/2012/298742
|View full text |Cite
|
Sign up to set email alerts
|

Shesher and Welala Floodplain Wetlands (Lake Tana, Ethiopia): Are They Important Breeding Habitats forClarias gariepinusand the MigratoryLabeobarbusFish Species?

Abstract: This study aims at investigating the spawning migration of the endemic Labeobarbus species and C. gariepinus from Lake Tana, through Ribb River, to Welala and Shesher wetlands. The study was conducted during peak spawning months (July to October, 2010). Fish were collected through overnight gillnet settings. A total of 1725 specimens of the genus Labeobarbus (13 species) and 506 specimens of C. gariepinus were collected. Six species of Labeobarbus formed prespawning aggregation at Ribb River mouth. However, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…The high percentage occurrence of fish in the wet season diet of the African clawless otter may be explained by the spawning migration behaviour for reproduction in their breeding sites to the rivers and shores. Anteneh et al (2012) reported that the spawning migration of fish from Lake Tana through rivers and wetlands has a wet season peak (July to October) while their spawning was also slowed by low water temperatures. This behavior might rendered the fish more vulnerable to predation in the wet season.…”
Section: Discussionmentioning
confidence: 99%
“…The high percentage occurrence of fish in the wet season diet of the African clawless otter may be explained by the spawning migration behaviour for reproduction in their breeding sites to the rivers and shores. Anteneh et al (2012) reported that the spawning migration of fish from Lake Tana through rivers and wetlands has a wet season peak (July to October) while their spawning was also slowed by low water temperatures. This behavior might rendered the fish more vulnerable to predation in the wet season.…”
Section: Discussionmentioning
confidence: 99%
“…The surface area of Welala is estimated about 110 ha, which is impounded by open water for along period of a year with maximum depth of 3m during rainy season. According to [4], its surface area was 159 hectares shirked by 47 % from what it was 298 ha in 1987. Welala wetland was imposed by one kebele only, Nabega Giorgis that has bylaw, to be assigned only for communal grazing land in contrast to Shesher wetland.…”
Section: Welala Natural Reservoirmentioning
confidence: 99%
“…This reservoir is estimated with an area of 500 hectares filled with water and free from vegetation cover due to its high relative depth that estimated of maximum depth 3m during the pick rainy season ( Figure 2). According to [4], the surface area of Shesher shirked by 91 % to 136 hectares from what it was 1557 hectares in 1987. The whole boundary of this reservoir was cultivated by the inhabitants with rice production at all water logged areas during the rainy seasons.…”
Section: Shesher Natural Reservoirmentioning
confidence: 99%
“…Shesher and Welala natural reservoirs are found just at the boundary of the lake in fogera floodplains of Fogera woreda of South Gondar zone (Figure 1). These are breeding sites mainly for Clarias gariepinus fish species but not endemic Labeobarbus species of Lake Tana [4]. Fishing activities during the breeding seasons (rainy seasons) and post rainy seasons are immense than ever, fishermen used spears and seining as fishing gear during these seasons respectively.…”
Section: Study Areamentioning
confidence: 99%
“…Shesher and Welala natural reservoirs are found just at the boundary of the lake in fogera floodplains of Fogera woreda of South Gondar zone ( Figure 1). These are breeding sites mainly for Clarias gariepinus fish species but not endemic Labeobarbus species of Lake Tana [4]. Fishing activities…”
Section: Study Areamentioning
confidence: 99%